5G Green Mobile Communication Networks - Ge, Xiaohu; Zhang, Wuxiong (Springer Nature Singapore : Imprint: Springer, 2019)
This book focuses on the modeling, optimization, and applications of 5G green mobile communication networks, aimed at improving energy efficiency and spectrum utilization in 5G systems. It offers a balance between theoretical analysis and engineering practice, providing in-depth studies of a number of major topics, such as energy consumption models, optimization, system design, implementation, and performance evaluation. It also discusses four aspects of green communication in detail: cellular networks, resource management, wireless transmissions and multi-media communications. Further, this unique book comprehensively and systematically discusses green optimization in wireless mobile communications. As such it is a valuable resource for researchers, engineers, and graduate students in various fields, including telecommunications engineering, electrical and electronic engineering, and computer engineering, particularly those interested in green communications.